2017
DOI: 10.1155/2017/7340143
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Anti‐Inflammatory Effects of Shungite against Ultraviolet B Irradiation‐Induced Skin Damage in Hairless Mice

Abstract: As fullerene-based compound applications have been rapidly increasing in the health industry, the need of biomedical research is urgently in demand. While shungite is regarded as a natural source of fullerene, it remains poorly documented. Here, we explored the in vivo effects of shungite against ultraviolet B- (UVB-) induced skin damage by investigating the physiological skin parameters, immune-redox profiling, and oxidative stress molecular signaling. Toward this, mice were UVB-irradiated with 0.75 mW/cm2 fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 32 publications
0
24
0
1
Order By: Relevance
“…Natural shungite is composed mainly of carbon (28-99%). Interestingly, after incubating shungite and fullerene stones in water, shungite water solutions were reported to have an antioxidant effect via the reduction of intracellular ROS production and the enhancement of antioxidant enzyme activities in animal cells [19]. The study also reported substantial improvements in the skin parameters (moisture, elasticity, roughness, pore size, pigmentation, and wrinkles) of shungite-treated groups, which were related to the recovery of total white blood cells.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Natural shungite is composed mainly of carbon (28-99%). Interestingly, after incubating shungite and fullerene stones in water, shungite water solutions were reported to have an antioxidant effect via the reduction of intracellular ROS production and the enhancement of antioxidant enzyme activities in animal cells [19]. The study also reported substantial improvements in the skin parameters (moisture, elasticity, roughness, pore size, pigmentation, and wrinkles) of shungite-treated groups, which were related to the recovery of total white blood cells.…”
Section: Discussionmentioning
confidence: 89%
“…Consistently, ROS-scavenging enzymes, such as GPx and SOD, in the shungite treatment group showed increased activity levels of 25% and 33% in skin lysate, respectively. Synthetically, these results led to an antioxidant and anti-inflammatory effect against UVB-induced skin damage in hairless mice [19].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Не только фуллерены, но и другие наноструктуры углерода способны играть роль антиоксиданта. Так, хорошо известно, что природный минерал шунгит содержит не фуллерены, а турбостратный углерод, который может нейтрализовывать действие УФ-облучения на кожу [66].…”
unclassified